2010
DOI: 10.1128/jcm.00659-10
|View full text |Cite
|
Sign up to set email alerts
|

Improved Identification of Epidemiologically Related Strains of Salmonella enterica by use of a Fusion Algorithm Based on Pulsed-Field Gel Electrophoresis and Multiple-Locus Variable-Number Tandem-Repeat Analysis

Abstract: Pulsed-field gel electrophoresis (PFGE) and multiple-locus variable-number tandem-repeat analysis (MLVA) are used to assess genetic similarity between bacterial strains. There are cases, however, when neither of these methods quantifies genetic variation at a level of resolution that is well suited for studying the molecular epidemiology of bacterial pathogens. To improve estimates based on these methods, we propose a fusion algorithm that combines the information obtained from both PFGE and MLVA assays to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…1). This high convergence is well recognized in previous studies, although combining PFGE and MLVA results has been shown to increase the DI (Torpdahl et al, 2007;Broschat et al, 2010;Kurosawa et al, 2012). Again, the application of more discriminatory methods would assist obtaining a correct interpretation of data.…”
Section: Discussionmentioning
confidence: 54%
“…1). This high convergence is well recognized in previous studies, although combining PFGE and MLVA results has been shown to increase the DI (Torpdahl et al, 2007;Broschat et al, 2010;Kurosawa et al, 2012). Again, the application of more discriminatory methods would assist obtaining a correct interpretation of data.…”
Section: Discussionmentioning
confidence: 54%
“…Thawed culture stock (1 ll) was added to 20 ll PCRs and cycle conditions included a 3-min initial denaturation at 95°C, followed by 30 cycles of 30 s at 95°C, 30 s at 52°C and 35 s at 72°C, followed by a 5-min final extension at 72°C. The putative E. coli-186 isolates (n = 105 confirmed/172 tested) recovered from the faecal samples were confirmed by pulsed-field gel electrophoresis analysis (Broschat et al 2010). Of calves inoculated with E. coli-25DtraM and E. coli-186, we detected the expected strains in five and six calves, respectively.…”
Section: Faecal Sample Collection Isolation and Enumeration And Idenmentioning
confidence: 68%
“…The putative E. coli ‐186 isolates ( n = 105 confirmed/172 tested) recovered from the faecal samples were confirmed by pulsed‐field gel electrophoresis analysis (Broschat et al . ). Of calves inoculated with E. coli‐25Δ traM and E. coli ‐186, we detected the expected strains in five and six calves, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…In MLVA, a need to develop a new set of loci for every species or serovar under investigation might be necessary. Moreover, some loci are ‘not stable’ and can ‘disappear’ from some strains or lineages what will result in an uninformative ‘zero’ allele [53]. …”
Section: Discussionmentioning
confidence: 99%